Training of Effective Online Marketing and Financial Management During the Pandemic for SMEs in Watudandang Village Nganjuk District - Yanuar Nugroho; Phima Ruthia Dwikesumasari; Bani Alkausar (Universitas Airlangga, 2020)
Covid-19, apart from affecting the income of big businesses, also affects micro, small and medium enterprises (MSMEs) due to a decrease in consumer purchasing power to the conventional strategies of MSMEs that are not ready to face the crisis. Until now, MSMEs in Watudandang Village are less orderly in the management of operational financial records so that the profits earned cannot increase the economic class of their business, besides that, marketing techniques for MSME products have been carried out online but have not mastered the tricks and strategies of how products can be easily searched so that they are suitable with consumer expectations. The method of implementing this program is carried out in a blended manner in the form of training in the preparation of financial reports for MSMEs and online product marketing assistance. This activity resulted in an increase in the competence of MSME players in analyzing profit and loss more precisely, thus providing an overview / perspective for MSME players to make policies regarding the course of their business operations. In addition, as a result of the impact of this pandemic crisis, MSME players have been able to take advantage of information technology to market their products online so that consumers will still look for these UMKM products.